Citizen Sociolinguistics: A Data Collection Approach for Hard-to-capture Naturally Occurring Language Data. Issue 3 (August 2020) - SturtzSreetharan, Cindi
Applying an approach termed "citizen sociolinguistics" offers a unique opportunity to capture a large corpus of naturally occurring language data, especially fleeting interactions. Drawing on citizen science innovations in the natural sciences, citizen sociolinguistics recruits and trains scientists to complete data-related tasks such as data collection. Additional benefits of the approach include inclusivity of diverse speakers and capacity to scale projects. Tested procedures for implementing citizen sociolinguistics are described, ethical challenges are considered, and other potential benefits and limitations to engaging the lay public in scientific research around language use are addressed.